Answer:
D.
Step-by-step explanation:
Find the average rate of change of each given function over the interval [-2, 2]]:
✔️ Average rate of change of m(x) over [-2, 2]:
Average rate of change = [tex] \frac{m(b) - m(a)}{b - a} [/tex]
Where,
a = -2, m(a) = -12
b = 2, m(b) = 4
Plug in the values into the equation
Average rate of change = [tex] \frac{4 - (-12)}{2 - (-2)} [/tex]
= [tex] \frac{16}{4} [/tex]
Average rate of change = 4
✔️ Average rate of change of n(x) over [-2, 2]:
Average rate of change = [tex] \frac{n(b) - n(a)}{b - a} [/tex]
Where,
a = -2, n(a) = -6
b = 2, n(b) = 6
Plug in the values into the equation
Average rate of change = [tex] \frac{6 - (-6)}{2 - (-2)} [/tex]
= [tex] \frac{12}{4} [/tex]
Average rate of change = 3
✔️ Average rate of change of q(x) over [-2, 2]:
Average rate of change = [tex] \frac{q(b) - q(a)}{b - a} [/tex]
Where,
a = -2, q(a) = -4
b = 2, q(b) = -12
Plug in the values into the equation
Average rate of change = [tex] \frac{-12 - (-4)}{2 - (-2)} [/tex]
= [tex] \frac{-8}{4} [/tex]
Average rate of change = -2
✔️ Average rate of change of p(x) over [-2, 2]:
Average rate of change = [tex] \frac{p(b) - p(a)}{b - a} [/tex]
Where,
a = -2, p(a) = 12
b = 2, p(b) = -4
Plug in the values into the equation
Average rate of change = [tex] \frac{-4 - 12}{2 - (-2)} [/tex]
= [tex] \frac{-16}{4} [/tex]
Average rate of change = -4
The answer is D. Only p(x) has an average rate of change of -4 over [-2, 2]